Lymph Scintigraphy and Pre- and Intraoperative Gamma Prone Measurements for Localization of Sentinel Lymph Nodes (SLN) in Breast Cancer - Brenner, W.; Ostertag, H.; Czech, N.; zum Felde, U.; Kampen, W. U.; Klutmann, S.; Bohuslavizki, K. H.; Lüttges, J.; Sprenger, A.; Henze, E. (Nuklearmedizin - NuclearMedicine, 2000)
Aim of this study was to prove the clinical value of nuclear medicine procedures to detect the sentinel lymph node (SLN) for SLN biopsy. Methods: In 132 patients with breast cancer we performed lymph scintigraphy of the breast as well as both pre- and intraoperative gamma probe measurements correlating the results with the findings of histopathology. Results: SLN were detectable in 62 of 110 patients according to a sensitivity of 56% when scanning was performed only at 1-2 h p.i. while the sensitivity increased to 86% (19 of 22 pts.) if sequential images were acquired up to 2 h p.i. One or more SLN were identified by a handheld gamma probe transcutaneously prior to surgery in 96% (113 of 118 pts.) of the patients who showed up with no clinically suspected lymph node metastases. Intraoperatively, in additionally 2 patients the SLN could be found resulting in a sensitivity of 97% (115 of 118 pts.). In only 3 patients with clinically no tumor spread to axillary lymph nodes no SLN could be identified by the probe. Skip lesions, i.e. lymph node metastases in patients with tumorfree SLN, occured in 2 cases: due to SLN biopsy in these patients lymph node staging was false negative compared to conventional staging by means of axillary lymph node dissection. Conclusion: The results demonstrate a high preoperative detection rate of SLN in patients with breast cancer using lymph scintigraphy and gamma probe measurements. Thus, nuclear medicine is capable of providing the basic requirements for SLN biopsy in the daily routine.
Keywords: Lymph scintigraphy; gamma probe; breast cancer; sentinel lymph node